Anomalous compliance of interpenetrating-phase composite of Ti and Mg synthesized by liquid metal dealloying. (15th March 2021) - Okulov, Ilya Vladimirovich; Wilmers, Jana; Joo, Soo-Hyun; Bargmann, Swantje; Kim, Hyoung Seop; Kato, Hidemi
Abstract: Low modulus biomaterials are in focus as potential candidates for biomedical implants ensuring a fast healing of hard tissues. The close match between elastic properties of an implant material and bone are critical to eliminate stress-shielding effect. In this study, we synthesized a low modulus interpenetrating-phase composite of Ti and Mg by liquid metal dealloying. Its Young's modulus value is in the range of that found for human bone which allows for biomedical applications of this material. Unexpectedly, the Young's modulus value of the composite (17.6 GPa) is several times lower than that of each individual constituent phases, namely, Mg (45 GPa) and Ti (110 GPa). Using micromechanical modelling, it is demonstrated that the origin of the anomalously low modulus can be related to a weakened interface between the constituents. Graphical Abstract: Image, graphical abstract